Development Of Export Of Organic Products Based On The Implementation Of Global G.A.P - A.A. Yadgarov; G.T.Yuldashev (Research Parks Publishers, 2021)
The article highlights the importance of international quality standards in the cultivation and export of organic products in the agricultural sector, as well as the current role of the Global G.A.P. standard. in ensuring the safety of agriculture